Combined Digital Signature with SHA Hashing Technique-based Secure System: An Application of Blockchain using IoT - K. Anju Aravind, B. Ravindra Naik, Ch. Siva Chennarao1 (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The Internet of Things (IoT) has become a popular computing technology paradigm. It is increasingly being utilized to facilitate human life processes through a variety of applications, including smart healthcare, smart grids, smart finance, and smart cities. Scalability, interoperability, security, and privacy, as well as trustworthiness, are all issues that IoT applications face. Blockchain solutions have recently been created to help overcome these difficulties. Therefore, this work describes the concept of providing security for payment processing involved in IOT devices and their service usage by applying Blockchain technology. Blockchain is a secured distributed cryptographic hashing technique which maintain transaction in a transparent and unalterable format. It maintains block of chained transaction and keeps on validating old and new transaction and if old hash matched then only transaction will be consider as successfully verified. All user’s transaction will be privacy protected and this same technique applied in this project to secure payment process happen between users and company services. All data in this project saved inside Blockchain and authentication and privacy will be performed by using DSA (digital signature algorithm) and SHA hashing technique. In this project there are two users called Service Providers and Service users.